2018
DOI: 10.1002/slct.201800440
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Emission Properties by π‐Stacking and Conformation Adjustment of an Imidazole‐Tethered Naphthalimide Derivative

Abstract: Solid state self-assemblies of 2,4-dinitrophenolate, 2,4,6-trinitrophenolate salts of N-(3-imidazol-1-yl-propyl)-1,8-naphthalimide (abbreviated as imidanap) have distinguishable p-stacking patterns, each stack influences fluorescence emission causing fluorescence quenching. It is found that the solid sample of nitrate or bromide salt of imidanap retains fluorescence properties of the parent compound. Photo-induced electron transfer process in solution gets prominence upon interactions of imidanap with hydrobro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Further, although interaction of pyrene and phenanthridine is necessary for FRET, it seems that higher degree of aromatic surfaces overlapping and cation-π interactions also yield excimer fluorescence quenching [22,[24][25]. This conclusion is strongly in line with experimental insight reported here and helps in explaining the observed excimer fluorescence quenching with a decrease in the solution pH value as well as with the stronger excimer fluorescence of Phen-Py-1 compared to Phen-Py-2.…”
Section: Computational Analysissupporting
confidence: 87%
“…Further, although interaction of pyrene and phenanthridine is necessary for FRET, it seems that higher degree of aromatic surfaces overlapping and cation-π interactions also yield excimer fluorescence quenching [22,[24][25]. This conclusion is strongly in line with experimental insight reported here and helps in explaining the observed excimer fluorescence quenching with a decrease in the solution pH value as well as with the stronger excimer fluorescence of Phen-Py-1 compared to Phen-Py-2.…”
Section: Computational Analysissupporting
confidence: 87%
“…The water molecules competes to set apart the ion pairs, hence the recovery of emission from the salt upon addition of water was possible. In a recent report, we observed that addition of water to analogous naphthalimide derivative N‐(3‐imidazol‐1‐yl‐propyl)‐1,8‐naphthalimide has shown enhancement of emission up to a particular concentration; whereas the emission quenching of the N‐(3‐imidazol‐1‐yl‐propyl)‐1,8‐naphthalimide with addition of water took place . In the present examples, only the quenching of emission were observed upon addition of water.…”
Section: Resultsmentioning
confidence: 94%
“…The emission of each compound L 1 or L 2 were quenched by H24dnp and H246tnp in a similar manner to the reported quenching of fluorescence of the N‐(3‐imidazol‐1‐yl‐propyl)‐1,8‐naphthalimide and N,N′‐ bis (3‐imidazol‐1‐yl‐propyl)naphthalenediimide . Hence, for a comparison the normalized emission intensity with respect to specific amount of two nitrophenol derivatives are plotted (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the factors resulting from the molecular arrangement in the crystal lattice, which influences the fluorescent properties, the occurrence of hydrogen bonds and π-π stacking interactions can be detected [ 8 ]. However, the literature is uncertain if the presence of these factors has a positive or negative effect on properties such as fluorescence quantum yield or fluorescence lifetime [ 9 , 10 , 11 , 12 , 13 ]. These occurrences are promoted by numerous complex mechanisms, such as aggregation-induced emission (AIE) or aggregation caused-quenching (ACQ), that can co-occur.…”
Section: Introductionmentioning
confidence: 99%